2016
DOI: 10.1017/s0144686x16000374
|View full text |Cite
|
Sign up to set email alerts
|

Living arrangement and cognitive decline among older people in Europe

Abstract: Family resources may play an important role in the wellbeing of older people. In this paper, we examine the association between living arrangement and cognitive decline among people over 65 living in different European countries. The underlined hypothesis is that living with others (i.e. spouse or/and children) vis-à-vis living alone may have a positive role in maintaining cognitive functioning, but also that such beneficial influence varies according to the circumstances. To this end, we used data from the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
(49 reference statements)
3
42
1
Order By: Relevance
“…Further empirical studies, in alignment with the cognitive reserve hypothesis have supported the proposition of relationships (e.g., marriage) acting as protective factors against age-associated cognitive decline, in comparison to living alone (Håkansson et al, 2009;Mousavi-Nasab et al, 2012). In accordance with these findings are the results from a longitudinal study by Mazzuco et al (2017), whose sample comprised of Northern Europeans (N = 1276). The researchers showed that co-residence with a partner or with adult children reduced cognitive decline in older adults in comparison to those living alone, even if their cognitive status was already being compromised.…”
Section: Introductionsupporting
confidence: 57%
“…Further empirical studies, in alignment with the cognitive reserve hypothesis have supported the proposition of relationships (e.g., marriage) acting as protective factors against age-associated cognitive decline, in comparison to living alone (Håkansson et al, 2009;Mousavi-Nasab et al, 2012). In accordance with these findings are the results from a longitudinal study by Mazzuco et al (2017), whose sample comprised of Northern Europeans (N = 1276). The researchers showed that co-residence with a partner or with adult children reduced cognitive decline in older adults in comparison to those living alone, even if their cognitive status was already being compromised.…”
Section: Introductionsupporting
confidence: 57%
“…Potential confounders were identified and selected based on theoretical assumptions and empirical findings of past literature [3,20]. The socioeconomic covariates included sex (male or female), age (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) or 60-64 years), spatial residence (rural or urban), employment status (unemployed or employed) and level of education (primary school/no attendance, secondary education or higher) and individual monthly income.…”
Section: Confounding Variablesmentioning
confidence: 99%
“…Between 2015 and 2050 the global population of people aged 60 + years is projected to almost double, reaching around 2.1 billion [1]. The number of older people residing in sub-Saharan Africa is projected to reach 161 million by 2050 [1] and the majority of these individuals are most likely to live alone and perhaps, socially isolated usually because they have outlived a partner or faced with intractable life circumstances such as retirement, functional impairment and gradual social change [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Potential confounders were identified and selected based on theoretical assumptions and empirical findings of past literature [3,20]. The socioeconomic covariates included sex (male or female), age (50-64 years or ≥65 years), spatial residence (rural or urban), employment status (unemployed or employed) and level of education (primary school/no attendance, secondary education or higher) and individual monthly income.…”
Section: Confounding Variablesmentioning
confidence: 99%
“…these individuals are most likely to live alone and perhaps, socially isolated usually because they will outlive their partners or faced with intractable life events such as retirement, daily activity limitations and gradual social change [2,3].…”
mentioning
confidence: 99%